Pengaruh Supervisi Kepala Madrasah Terhadap Kedisiplinan Guru di MTs Guppi Samata Kec. Somba Opu Kab. Gowa - Ishak Ishak; Muhammad Yusuf Hidayat; Syamsuddin Syamsuddin (Kelola: Journal of Islamic Education Management, 2019)
This study aims to determine the effect of supervision delivered by Madrasah Principal on teacher discipline in MTs Guppi Samata, Kec. Somba Opu, Gowa, South Sulawesi. This research is a field research with quantitative research design and quantitative approach. The research used questionnaire as a data collection technique that included three stages (preparation, implementation, and final stages), and were prepared using a Likert scale. The data analysis technique used is descriptive and inferential statistical analysis techniques. The results of the data analysis showed that there was an effect of the supervision of the Madrasah principal on the discipline of MTs Guppi Samata teachers in Kec. Somba Opu, Gowa, South Sulawesi.